PENGEMBANGAN BPS (BUDAYA PENARUHAN SEPATU) DALAM PENDIDIKAN KARAKTER PESERTA DIDIK - Ni Made Ina Pratiwi; Kadek Ari Setia Utama Putra; Ni Kadek Ayu Seri Astiti; Ni Komang Sutriyanti (GUNA WIDYA: JURNAL PENDIDIKAN HINDU, 2021)
SMA Negeri Bali Mandara issued a regulation whereby items that were not properly guarded or neglected would be brought to the principal's office to be followed up and had to come face to face and provide logical reasons to the principal for those who wanted their items back. This regulation was issued due to the lack of awareness of students in appreciating the items provided by the school. The objectives to be achieved in this study are to determine the impact of the implementation of the shoe-placing culture regulations on the character of SMA Negeri Bali Mandara students, knowing the possible impact of the implementation of the Shoe-Putting Culture in addition to the SMA Negeri Bali Mandara, knowing how to implement this rule if this rule is applied in other schools. as a medium to encourage a better character. This research instrument includes interviews, documentation, and questionnaires. The data obtained were analyzed using qualitative, quantitative, and descriptive methods. The results of this study are as follows: The culture of placing shoes in SMA Negeri Bali Mandara can influence foreign schools to implement this culture for the realization of good student character and the form of implementation of the existence of a shoe-placing culture related to student character education with the percentage of the influence of the shoe-betting culture on outside schools of 83.2% and implementation of 78.8% showed that students played a very important role in the implementation of this Shoe-Putting Culture.